2023
DOI: 10.1088/2515-7655/acb176
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic and magnetocaloric properties in distorted RE 2NiTiO6 double perovskite compounds

Abstract: The magnetocaloric effect (MCE) based Magnetic refrigeration (MR) was considered a novel energy-efficient and environmentally benign cooling method. However, the lack of suitable magnetic solids has slowed the development of its practical applications. We herein fabricated the RE2NiTiO6 (RE = Gd, Tb and Ho) double perovskite (DP) compounds and systematically determined their structural, magnetic and magnetocaloric properties by experimental determination and density functional theory (DFT) calculations, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Wyc. positions, bond lengths, and bond angles which are in good agreement with the reported values in the octahedral oxygen environment of related double perovskites [57,58]. The absorption peaks at 439 cm −1 , 504 cm −1 , and 584 cm −1 with the prominent peak at 706 cm −1 can be ascribed to the stretching and bending vibrations of the metal-oxygen (Ni/Cr-O) bonds within the NiO 6 /CrO 6 octahedra of the YNCO compound [13,59,60].…”
Section: Crystallographic Structure Analysissupporting
confidence: 90%
“…Wyc. positions, bond lengths, and bond angles which are in good agreement with the reported values in the octahedral oxygen environment of related double perovskites [57,58]. The absorption peaks at 439 cm −1 , 504 cm −1 , and 584 cm −1 with the prominent peak at 706 cm −1 can be ascribed to the stretching and bending vibrations of the metal-oxygen (Ni/Cr-O) bonds within the NiO 6 /CrO 6 octahedra of the YNCO compound [13,59,60].…”
Section: Crystallographic Structure Analysissupporting
confidence: 90%
“…It was found that in case of Gd 2 NiTiO 6 compound MCE properties are better than other two compounds. 35 The transition temperature and magnetocaloric effect can be enhanced by substituting non-magnetic Ti 3+ ion in Gd 2 CoMnTiO 6 compound by Zheng et al 36 It was found that MCE enhanced from 16.64 J kg −1 K −1 to 27.16 J kg −1 K −1 under Δ H = 6 T at cryogenic temperature. Patra et al 37 reported the synthesis of Ho 2 CoMnO 6 nanorod by using hydrothermal route and magnetocaloric effect gives a change in entropy value of 12.4 J kg −1 K −1 at low temperature for 7 T.…”
Section: Introductionmentioning
confidence: 99%
“…25 Among the double perovskite families, R 2 MMnO 6 (R = rare earth element, M = Ni, Co) has recently attracted substantial interest due to its controllability of magnetic and electronic properties. 26,27 These DP compounds contain Co 2+ ions with electronic conguration d 7 tse 2 g and Mn 4+ with electronic conguration d 3 t 2 g 3 e 0 g , which exhibit ferromagnetic ordering due to Co 2+ and Mn 4+ superexchange interactions. 28,29 These types of DP compounds are mostly ferromagnetic and insulating, with the formation of ferromagnetic cluster.…”
Section: Introductionmentioning
confidence: 99%
“…other industrial gases [13][14][15][16][17][18][19][20][21][22][23][24][25]. The emerging magnetocaloric liquefaction technology is in principle more efficient [5,[26][27][28][29][30][31][32], making the promise of hydrogen fuel being affordable for the society to reach climate-neutrality.…”
Section: Introductionmentioning
confidence: 99%